Penggunaan Media Elektronik Dalam Perdagangan Manusia Lintas Negara - Novia Andriani; Andi Aina Ilmih (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Human trafficking is an increasingly prevalent global issue, and social media has become a new tool for perpetrators to deceive and exploit victims. This research analyzes two main aspects: how social media becomes a means of fraud that leads to human trafficking, and effective protection and rehabilitation models for victims who are successfully released. First, this research examines various modes of fraud via social media that lead victims into human trafficking. Various platforms such as Facebook, Instagram and Twitter are used to deceive victims with the promise of promising jobs, marriage or a better life. Second, this research evaluates the protection and rehabilitation models available to victims of human trafficking. A comprehensive approach that includes legal, psychological, and socioeconomic assistance is essential to help victims recover and rebuild their lives. It is hoped that this research will contribute to a better understanding of the role of social media in human trafficking, as well as encourage the development of more effective protection and rehabilitation models for victims.